Implementasi Pembelajaran Aktif Berorientasi Mikir (Mengamati, Interaksi, Komunikasi, dan Refleksi) di SD Muhammadiyah 12 Medan - Elfrianto Elfrianto; Ismail Saleh Nasution; Eko Febriansyah Siregar; Achmad Yuhdi (Pelita Masyarakat, 2020)
Muhammadiyah Development Partnership Program (PKPM) through the internal funding of Muhammadiyah University of North Sumatra was conducted to assist teachers in managing active learning through the MIKIR strategy (Experiencing, Interaction, Communication, and Reflection). The PKM activity partners are two schools from among the UMSU partner schools, namely SD Muhammadiyah 12 Medan. Specific targets to be achieved through the implementation of PKPM activities produce professional and skilled teachers in managing active learning so that the learning provided is more interesting and meaningful for students. The approach method offered in this PKPM activity is training and mentoring with stages: 1) Initial meeting to partner teachers in the activity of equality perception about active learning through MIKIR techniques, 2) Intensive training and mentoring, 3) classroom practice in partner elementary schools, and 4) evaluation of the results of activities. Each stage is carried out maximally, so that the competency of the assisted teacher becomes better in managing active learning which is oriented towards MIKIR activities